Training to Raise Awareness of Dadaman Coffee Coffee through My Google Business - Pertiwi, Widya Nur Bhakti; Satyanegara, Diqbal; Fadhilah, Fadhilah; Hisyam, Muhammad (EQUATOR SINAR AKADEMIA, 2024)
Karya Muda I Farmers Group, Ciomas District, Serang Regency, has a superior product of robusta coffee. The coffee has good quality, and has won a champion at the provincial level. However, currently, not many people know about the existence of Kopi Dadaman, Citaman Village. As an effort to increase public awareness of Kopi Dadaman, this community service activity was carried out by creating a business profile and also maps via Google. With this, it is hoped that Kopi Dadaman will appear on the Google search engine when potential consumers search. The community service method is carried out by conducting training, and also mentoring the Karya Muda Farmers Group, so that in the future they can manage Google Business independently. The results of the training are that Kopi Dadaman has a Business Profile and Maps on Google.